2016
DOI: 10.1038/srep25476
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated hedgehog pathway signaling is inhibited by the smoothened antagonist LDE225 (Sonidegib) in chronic phase chronic myeloid leukaemia

Abstract: Targeting the Hedgehog (Hh) pathway represents a potential leukaemia stem cell (LSC)-directed therapy which may compliment tyrosine kinase inhibitors (TKIs) to eradicate LSC in chronic phase (CP) chronic myeloid leukaemia (CML). We set out to elucidate the role of Hh signaling in CP-CML and determine if inhibition of Hh signaling, through inhibition of smoothened (SMO), was an effective strategy to target CP-CML LSC. Assessment of Hh pathway gene and protein expression demonstrated that the Hh pathway is activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 57 publications
2
69
0
Order By: Relevance
“…More recently, similar results were obtained using SMO inhibitors in human CML samples in vitro and in vivo using xenografts in immunocompromised NOD scid gamma (NSG) mice 62 .…”
Section: Hedgehog Signallingsupporting
confidence: 59%
See 1 more Smart Citation
“…More recently, similar results were obtained using SMO inhibitors in human CML samples in vitro and in vivo using xenografts in immunocompromised NOD scid gamma (NSG) mice 62 .…”
Section: Hedgehog Signallingsupporting
confidence: 59%
“…Several studies have implicated the hedgehog pathway in the maintenance (selfrenewal) and proliferation of the LSC [60][61][62] , where Smoothened (SMO) is a critical mediator. Hedgehog binding to Patched (PTCH) activates SMO which in turn activates the transcription factor GLI1.…”
Section: Hedgehog Signallingmentioning
confidence: 99%
“…The targeting of the Hh pathway, known to be activated in CD34+ CP‐CML, through the inhibition of SMO using LDE225 alone or in association with nilotinib, was effective in reducing the number and the self‐renewal capacity of CML LSCs in vitro, without effects on normal HSCs . A phase I clinical trial investigated the feasibility of administration of LDE225 with nilotinib in patients with CML who have failed other TKI treatments (NCT01456676).…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of Nilotinib in CML-CP patients can also be attributed, in part, to its anti-SMO activity reported here and its ability to inhibit CSC growth. In fact, a recent study 68 demonstrated alterations of Hh pathway gene expression in a subpopulation of CML-CP patients: the negative modulators GLI3 and SUFU genes were down-regulated and the Hh target genes CCNB2, STIL, FOXM1 and GLI1 genes were up-regulated.…”
Section: Discussionmentioning
confidence: 98%